Up, Up, Up! : it's apple-picking time - Shapiro, Jody Fickes (New York : Scholastic Inc, 2003)
Myles and his family go to his grandparents' apple ranch, where they have a wonderful time picking and selling apples together.
Keywords: Apples -- fiction